Design and Characterization of a Roof-Mounted Compound Parabolic Concentrator - Mc Cormack, Sarah; Ortega, Anita; Chandra, Subhash (My University, 2021)
This paper presents the design, fabrication and performance of a roof mounted compound parabolic concentrators (CPC) for electricity generation. A truncated Asymmetric Compound Parabolic Concentrator with concentration ratio of 1.83, acceptance -half angles of 60° and an absorber width of 125 mm has been designed, constructed and experimentally characterized on the roof of the Simon Perry Building at Trinity College Dublin, Ireland (53.344295, -6.252416). A CPC and a PV systems were tested under outdoor conditions with 4-cell PV strings. The first challenge was to determine the power generation, efficiency and temperature of both systems and compare the results. The experiment revealed that at solar incident radiation of 800 W/m2, the CPC system increased the power and efficiency by 34 % (power by factor 1.34) and 22 % (efficiency by factor 1.22) respectively, compared with PV system. However, the solar cell temperature in CPC system increased by 74 % (temperature by factor 1.74). In order to analyze the temperature, a convective cooling CPC system was tested. The result showed that when the temperature increased by 22 % (temperature by factor 1.22) compared with the PV system, the power and efficiency improved by 84 % and 65 %, respectively.
World Renewable Energy Congress
PUBLISHED
Keywords: Building integration; Compound parabolic concentrator; Photovoltaics